2022
DOI: 10.12998/wjcc.v10.i11.3490
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Cladosporium infection coexisting with subcutaneous Corynespora cassiicola infection in a patient: A case report

Abstract: BACKGROUND Cladosporium and Corynespora cassiicola ( C. cassiicola ) infections rarely occur in humans. Mutations in human caspase recruitment domain protein 9 (CARD9) are reported to be associated with fungal diseases. Pulmonary Cladosporium infection coexisting with subcutaneous C. cassiicola infection in a patient with a CARD9 mutation has not been reported in the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…and Kazachstania sp. were also found, the presence of which were previously reported in human infection cases [ 66 68 ].…”
Section: Discussionsupporting
confidence: 65%
“…and Kazachstania sp. were also found, the presence of which were previously reported in human infection cases [ 66 68 ].…”
Section: Discussionsupporting
confidence: 65%
“…Studies have shown that C. cassiicola has the potential to be vascular invasive and may lead to disseminated infections in immunodeficient hosts ( Lv et al., 2011 ). Three cases of CARD9 deficiency causing infection with this fungus had been reported, and the treatment of antifungal infection was ineffective in two of them ( Yan et al., 2016 ; Arango-Franco et al., 2018 ; Wang et al., 2022 ). Notably, most cases were from Asia.…”
Section: Discussionmentioning
confidence: 99%
“…C. cassiicola causes multiple diseases in plants ( 39 ). It also rarely causes human phaeohyphomycosis, affecting diabetic ( 40 ), CARD9-deficient ( 4 , 21 , 41 ), and apparently immunocompetent patients ( 42 44 ). Human Dectin-1 deficiency caused by p.Y238* homozygosity was previously associated with vulvovaginal candidiasis and onychomycosis ( 19 ).…”
Section: Discussionmentioning
confidence: 99%